Distress and Psychosocial Needs in Patients Accessing a Cancer Day Surgery Division: Implications for Clinical Decision Making - Arnaboldi, Paola; Riva, Silvia; Vadilonga, Valeria; Tadini, Liliana; Magon, Giorgio; Pravettoni, Gabriella (Frontiers in Psychology, 2016)
Introduction: The Distress Thermometer was built and validated for screening cancer patients for distress, as suggested by the National Comprehensive Cancer Network. The current work was designed to measure the rates of distress in a sample of patients being hospitalized in a multidisciplinary outpatient surgery clinic. Objective: To measure the rates of distress in a sample of patients referring to a multidisciplinary day surgery division in a comprehensive cancer center based in Northern Italy. Methods: A total of 177 patients were asked to fill in the distress thermometer (DT) before surgery. Results: Out of 177 patients, 154 (87%) patients completed the Distress Thermometer. While 13% of the patients indicated a total absence of distress, more than half of the sample declared a moderate or high distress. A total of 55% of patients presented at least three difficulties in the Problem List Checklist. Distress was not correlated with age or other medical and clinical variables. Number of emotional problems was the best predictor of distress at admission (beta=.655, p=.000). Conclusions: Screening for distress in a day surgery multidisciplinary oncology division is feasible and a relevant percentage of patients can be identified as clinically distressed. Outcomes also highlight the impact of age and precise physical and psycho-social signs as prognostic indicators of clinically significant distress. Measurement of distress and associated problems list represent the preliminary endpoint toward adequate recommendations that contribute to taking care of distress in cancer patients in cost-effective clinical setting.